PERKEMBANGAN PENGOLAHAN KOPI ARABIKA GAYO MULAI DARI PANEN HINGGA PASCA PANEN DI KAMPUNG SIMPANG TERITIT TAHUN 2010-2017 - Yudi Wan Teniro; Zulfan .; Husaini . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACT The research entitled "The Development of Gayo Arabica Coffee Processing From Harvest to Post Harvest in Kampung Simpang Teritit, 2010-2017", this raises the problem of how the process of coffee processing development Gayo arabica harvest, Gayo arabica coffee processing process post-harvest, Gayo arabica coffee process and constraints in the process of Gayo arabica coffee in Kampung Simpang Teritit. This study aims to know the process of development of Gayo arabica coffee harvest time, want to know the process of development of arabica coffee Gayo post harvest, the factors causing the development of Gayo arabica coffee processing and constraints in the process of Gayo arabica coffee processing. The method used is history with Qualitative approach, while the data collection techniques using libraly research (study library) and field research that includes observation, documentation, and interviews. Based on the research that has been done, the results obtained as follows: many indicators that cause the process of development during the harvest that is easy access to the harvest location because it has made the way to the farmers' gardens and the average farmers also have a motorcycle for the garden , the completeness of the pemetikan equipment that is more easily found because it can be created by itself, the easy process of picking because it has been studied and practiced hereditary so it already has the technique and system pattern itself to the process during the harvesting period. It is easy to post-harvest because of the development of the coffee industry tools that are more easily obtainable for purchase and use such as coffee leather machine, the easy way of using the machine because there are already instructions how to use, the more productive production land due to the increasing number of farmers caused by the plantation rental system applied by the owner of the garden, The increasing number of coffee processing plants caused by the increasing demand for Arabica coffee production in the market so that the community make coffee plants. facilitate farmers to produce coffee in large quantities because there are already factories that are willing to accommodate and process coffee, while the obstacles in coffee production is the lack of attention from the government, processing service, the expensive tools of the coffee industry, lamabatnya coffee production during the rainy season, in the coffee world is still not consistent.       Keywords:Development, Processing, Coffee, Arabica.